Who Chooses Best? Explaining the Interactive Effect of Culture and Decision Maker on Children's Intrinsic Motivation. (May 2015) - Rudy, Duane; Sheldon, Kennon M.; Li, Yaoran; Kamble, Shanmukh; Bi, Xi; Palermo, Francisco
In previous research, Asian Americans had higher levels of intrinsic motivation than European Americans when their mothers made choices for them. However, European Americans had higher levels of intrinsic motivation than Asian Americans when they made choices for themselves. We attempted to explain this effect by examining cultural differences in social perceptions of the choice situation in two studies. Study 1 found that feelings of closeness with parents and beliefs about who has better long-term foresight mediated the predicted group differences in intrinsic motivation in a parent-choice condition when comparing Indian and Chinese undergraduates with European American undergraduates. However, perceptions of how acceptable it is for the decision maker to make the choice mediated group differences in intrinsic motivation in a personal-choice condition. Although there were some exceptions, Study 2 generally replicated these findings in a comparison of Indian and European American undergraduates, and showed that cultural differences in beliefs about how accurately the decision maker knows and takes into account the participants' immediate preferences played an additional mediating role in the personal-choice condition, as did personal foresight. These studies suggest that cultural differences in how children construe decision making affect the relationship of such decision making to resultant intrinsic motivation.